Evidence, history, and the Great War : historians and the impact of 1914-18 - Braybon, Gail (Berghahn Books, 2003)
"While Britain may have suffered a surfeit of war books, many telling much the same story, there is far less written about the impact of the Great War in other combatant nations. Its history was long suppressed in both fascist Italy and the communist Soviet Union: only recently have historians of Russia begun to examine this conflict, which killed, maimed and displaced so many millions. Even in France and Germany, the experience of 1914-18 has often been overshadowed by the Second World War." "The Great War's social history is now ripe for reassessment and revision. The essays in this volume incorporate a European perspective, engage with the historiography of the war, and consider how the primary textural, oral and pictorial evidence has been used - or abused. Subjects include the politics of shellshock, the impact of war on women, the plight of refugees, food distribution in Berlin and portrait photography, all of which illuminate key debates in war history."--Jacket